(untitled) (Journal of Contemporary Educational Policies and Practices, 2022)
It has been around 15 years since the commencement of lesson study for the learning community (LSLC) in Vietnam. It started at several pilot schools in Bac Giang province, and today it is practised all over the country. While some pilot schools emerged with high-quality practices, the speed of actual changes in the practices still remains slow. This is because, as the author has found, the following conceptions persist among the policymakers, school leaders and teachers: (a) LSLC requires changing teaching techniques; (b) LSLC is a lesson demonstration, and (c) LSLC is a one-day event. This article addresses these conceptions and argues that LSLC should be considered a fundamental, long-term, and holistic school reform approach based on democratic principles and excellence. To overcome these limitations, it is critical for the practitioners, researchers and policymakers to have networks to share their experiences, be informed about the practices and theories, and research into LSLC more deeply – to even learn from the practitioners and researchers in other countries too.